Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26-29, 2023, Los Angeles, California - Montoya, Brina; Rathje, Ellen M.; Wayne, Mark H. (GSP (Series), 2023)
The first volume of six Geotechnical Special Publications (GSPs) containing papers from the 2023 Geo-Congress. Includes 61 peer-reviewed papers on topics related to geotechnics of natural hazards including: earthquake engineering and soil dynamics; geotechnics of soil erosion; landslide hazards; risk assessment and management; shake and bake; and wildfire hazards.